Diagnostic accuracy of Diabetes in Pregnancy Study Group of India criteria for the screening of gestational diabetes mellitus in primary care setting - Nitya Balagopalan; Rambha Pathak; Farzana Islam; Aruna Nigam; Prem Kapur; Sarita Agarwal (Wolters Kluwer Medknow Publications, 2021)
Introduction: Although the Diabetes in Pregnancy Study Group of India (DIPSI) criterion is recommended by the Government of India guidelines, there is lack of consensus on a universal criterion for diagnosis of gestational diabetes. This has led to a wide variation of pregnant women being diagnosed with gestational diabetes mellitus (GDM). The WHO 1999 and International Association of Diabetes and Pregnancy Study Groups (IADPSG) criteria are widely used globally and in India as well. The objective of this study was to evaluate the diagnostic accuracy of DIPSI criteria in comparison to WHO 1999 and IADPSG criteria for diagnosis of GDM. Materials and Methods: A community-based study was conducted for a period of 1 year. Oral glucose tolerance test was done on 506 pregnant women identified through house-to-house survey. The proportion of GDM cases by WHO, IADPSG, and DIPSI criteria was calculated. The diagnostic accuracy of DIPSI criteria was assessed by calculating sensitivity, specificity, and predictive values taking WHO and IADSPG criteria as gold standard. Results: The prevalence of GDM was 14.2% by WHO criteria, 13% by DIPSI criteria, and 27.3% by IADPSG criteria; 10.3% were diagnosed by all the three criteria. The sensitivity and specificity of DIPSI criteria when the WHO criteria was taken as the gold standard was found to be 86.1% and 99.08%. The sensitivity and specificity of DIPSI criteria when the IADPSG criteria was taken as gold standard was found to be 44.93% and 98.91%, respectively. Conclusion: The prevalence of GDM is found to be much higher by IADPSG criteria as compared to the WHO and DIPSI criteria. The single-step approach DIPSI criteria have good diagnostic accuracy and can be used in epidemiological studies and are feasible for diagnosis of GDM in primary care settings.